2022
DOI: 10.1093/hr/uhac136
|View full text |Cite
|
Sign up to set email alerts
|

A natural mutation of the NST1 gene arrests secondary cell wall biosynthesis in the seed coat of a hull-less pumpkin accession

Abstract: Hull-less pumpkins (Cucurbita pepo L.) are naturally occurring novel variants known as oilseed or naked-seeded pumpkins, and are characterized by the absence of a normal lignified seed coat. Due to a specialized seed coat structure, these variants serve as a good model for studying seed coat formation and simplify the processing of pumpkin seeds. However, causal genes for this hull-less trait still remain unknown. Here, by Bulked Segregant Analysis (BSA) and fine mapping, we found that mutation of a single gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…Based on the watermelon germplasms preserved in the National Mid-Term Genebank for Watermelon and Melon (Zhengzhou, China), egusi watermelon with a typical egusi type seed coat is shown in Figure 1 . The type 1 class of seeds with thin seed coats and flat edges looks morphologically similar to the hull-less seeds in pumpkin ( Lyu et al., 2022 ), which will be the focus of our research in the present study. The hull-less trait is an important trait in seed crops.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Based on the watermelon germplasms preserved in the National Mid-Term Genebank for Watermelon and Melon (Zhengzhou, China), egusi watermelon with a typical egusi type seed coat is shown in Figure 1 . The type 1 class of seeds with thin seed coats and flat edges looks morphologically similar to the hull-less seeds in pumpkin ( Lyu et al., 2022 ), which will be the focus of our research in the present study. The hull-less trait is an important trait in seed crops.…”
Section: Introductionmentioning
confidence: 83%
“…The partial egusi seed type in watermelon (unique egusi seed type in the present study) is similar to the hull-less trait in seed crops. Previous studies showed that one major gene, a minor gene with modifiers, or a polygenic model controlled the hull-less trait in other seed crops, such as pumpkin ( Chahal et al., 2022 ; Lyu et al., 2022 ), barley ( Taketa et al., 2008 ), oil palm ( Singh et al., 2013 ), and maize ( Wang et al., 2005 ). In the present study, two genes with inhibitory epistasis were found to be responsible for egusi seeds in watermelon as evidenced by the F 2 ratio (13:3) and confirmed by the phenotype and genotype in the BC 1 F 2 population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations